Do androids dream of electric cars? : public transit in the age of Google, Uber, and Elon Musk - Wilt, James (Between the Lines, 2020)
"Public transit in North America is in crisis. Ridership is down, fares are up, breakdowns more frequent, and in some cities trains are delayed because the tracks are literally on fire. Meanwhile, ride-sharing platforms like Uber and Lyft offer an alternative to standing on a crowded bus. And the electric and self-driving car manufacturers like Tesla and Google's Waymo promise a sustainable future without accidents caused by human error. But does Silicon Valley really have the right plans for moving us around and saving the planet? James Wilt takes a closer look at the state of public transit in North America and the devious ways that corporations have worked to dismantle our public systems. He provides hopeful answers to the question of how we might make public transit affordable, equitable, sustainable, and efficient."--